English for Academic Communication - Asiah, Kassim; Hafizoah, Kassim; Fathiah Izzati, Mohammad Fadzillah; Hamizah, Zahari; Mohd Shafiq, Abdul Jabar; Nur Syafawati, Sabuan; Suriya Kumar, Sinnadurai (Penerbit UMP, 2018)
The module comprises four units for all proficiency skills; listening, reading, speaking and writing.